FLOW OF DRUG ALLERGIES IN PEDIATRICS: A DESCRIPTIVE STUDY - Frota Coelho, Vanda; Ferreira de Lima, Diogo Thomas; da Silva Nogueira, Tiago; Menezes Azevedo, Maria de Fátima; Macatrão Nogueira Nunes, Luciana; Vale Francelino, Eudiana; Morais Borges, Karla Deisy (Cadernos ESP, 2025)
Introduction: The flow of care within drug allergies has been an enlightening process when the intention is to promote better quality in the diagnosis of pediatric patients. The Center for the Study of Medication and Food Allergy (CEAMA) has been in partnership for some time now with its theoretical expertise in information on the area of pharmacodermias and their insertion into practice, in collaboration with the Albert Sabin Children's Hospital (HIAS) and the Immunoallergology Outpatient Clinic becomes essential in the daily lives of professionals who work in this environment. Objectives: describe a flowchart of care for suspected pharmacodermias in inpatients and outpatients at the HIAS. Methods: The observational study had three phases from April to December 2023: 1) Meeting to prepare the questionnaire. 2) Distribution of the questionnaire via email to physicians after ethical approval. 3) Preparation of the service flow to optimize the service. Results: 144 emails were sent, with 38 responses received. With the data collected, a flowchart for implementation was created. Conclusion: The creation of the service flow can benefit patients and serve as a reference for other institutions, improving the quality of medical care.
Keywords: Flowchart; Drug Allergy; Pediatric Hospital